TENCON 2006 - 2006 IEEE Region 10 Conference 2006
DOI: 10.1109/tencon.2006.343754
|View full text |Cite
|
Sign up to set email alerts
|

On Self-Organizing Map Based Classification of Insect Neurons

Abstract: In this paper, a systematic method based on selforganizing maps is presented to classify interneurons of silkworm moths. Denseness of branching structures and existence of thick main dendrites are quantified by six fractal dimension values and three values calculated from images to which fundamental processing techniques are applied, respectively. Such values are employed as nine elements in training data for a map. The classification result is obtained as clusters with units in the trained map. Experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…For example, 153 antennal lobe local interneurons have been registered in the database and classified into five types (Seki and Kanzaki, 2008 ). This classification did correspond to the computational classification by fractal dimension calculated using the box counting method (Urata et al, 2006 ). Anatomical identification and classification have also been done in neuronal populations in the mushroom body, the center of learning and memory, and the lateral accessory lobe, the premotor network in the insect brain, based on 109 and 120 registered neurons, respectively (Fukushima and Kanzaki, 2009 ).…”
Section: Reconstruction Of Insect Sensory Networksupporting
confidence: 57%
“…For example, 153 antennal lobe local interneurons have been registered in the database and classified into five types (Seki and Kanzaki, 2008 ). This classification did correspond to the computational classification by fractal dimension calculated using the box counting method (Urata et al, 2006 ). Anatomical identification and classification have also been done in neuronal populations in the mushroom body, the center of learning and memory, and the lateral accessory lobe, the premotor network in the insect brain, based on 109 and 120 registered neurons, respectively (Fukushima and Kanzaki, 2009 ).…”
Section: Reconstruction Of Insect Sensory Networksupporting
confidence: 57%
“…(i) An analysis of 153 local interneurons in the AL that were registered in the BoND revealed that the AL consists of five types of local interneurons [7]. Similar results were obtained by fractal analysis using the box-counting method with a self-organization map [15]. (ii) Principle component analysis of 156 projection neurons (PNs) in the AL revealed that olfactory responses are translated into spatial and temporal patterns in the glomeruli of the AL [12].…”
Section: Bombyx Neuron Database (Bond)mentioning
confidence: 52%